Struktur Hujjah Al-Qira’at Syekh Mahfudz Al-Tarmasi Dalam Kitab Gunyah Al-Talabah Bi Syarh Al-Tayyibah (Analisis Teori Argumentasi pada Q.S. Al-Fatihah): Structure of the Hujjah Al-Qira'at of Sheikh Mahfudz Al-Tarmasi in the book Gunyah Al-Talabah Bi Syarh Al-Tayyibah (Analysis of Argumentation Theory in Q.S. Al-Fatihah) - Muiz, Abdul; Huda, M. Khozinul (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2025)
This study aims to produce a model of the Structure of Hujjah al-Qira’at of Sheikh Mahfudz al-Tarmasi. To find out the authority of Muqri’ nusantara, the authority of Hujjah al-Qira’at (Tawjih al-Qira’at) of Sheikh Mahfudz is urgently studied as a model, considering that he lived in an era of strengthening the network of Middle Eastern and Indonesian Ulama. With the analysis of Argumentation theory, the researcher wants to trace the structure of the argument of Hujjah al-Qira’at of Sheikh Mahfudz, its originality and dynamics/Tajdid as evidence of his authority. The analysis methods used are interpretive and inductive methods. The results of the study show that first, Sheikh Mahfudz has authority in the field of Qira’at Science both riwayah and dirayah. In terms of riwayah he has a chain of chains that are connected to the Prophet. In terms of his personality, he has an authoritative Hujjah al-Qira’at based on a very complex Hujjah component in relying on qira’at to previous muqri’ who are also authoritative. Second, based on the theory of argumentation, the authority of Sheikh Mahfudz’s argument in Hujjah al-Qira’at lies in the systematic and completeness of his argumentation structure pattern which is more dynamic than his predecessors, in this case he has originality and carries out Tajdid.